The Death of a Prophet : The End of Muhammad's Life and the Beginnings of Islam - Shoemaker, Stephen J., 1968- (Book collections on Project MUSE., 2012)
In this study Stephen J. Shoemaker investigates contradictory traditions about the end of Muhammad's life in the Islamic and non-Islamic sources of the seventh and eighth centuries.